2007
DOI: 10.1007/s00251-007-0201-2
|View full text |Cite
|
Sign up to set email alerts
|

MHC class I A region diversity and polymorphism in macaque species

Abstract: The HLA-A locus represents a single copy gene that displays abundant allelic polymorphism in the human population, whereas, in contrast, a nonhuman primate species such as the rhesus macaque (Macaca mulatta) possesses multiple HLA-A-like (Mamu-A) genes, which parade varying degrees of polymorphism. The number and combination of transcribed Mamu-A genes present per chromosome display diversity in a population of Indian animals. At present, it is not clearly understood whether these different A region configurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
142
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(161 citation statements)
references
References 51 publications
14
142
1
4
Order By: Relevance
“…One of these alleles, Mamu-A1*2601, was also recently detected in Chinese rhesus macaques by Otting et al (2007). The Mamu-A4*1403 allele reported here is consistent with being an Indian origin macaque allele, lacking the stop codon in exon 5 that was present in the only previously reported Chinese Mamu-A4 allele (Otting et al 2007). The degree of Mamu-B cDNA sharing between rhesus macaques of different geographic origin is not currently known, and there is only limited information on Mamu-A allele sharing.…”
Section: Potential Admixture Of Chinese-and Indian-origin Rhesus Macasupporting
confidence: 87%
See 2 more Smart Citations
“…One of these alleles, Mamu-A1*2601, was also recently detected in Chinese rhesus macaques by Otting et al (2007). The Mamu-A4*1403 allele reported here is consistent with being an Indian origin macaque allele, lacking the stop codon in exon 5 that was present in the only previously reported Chinese Mamu-A4 allele (Otting et al 2007). The degree of Mamu-B cDNA sharing between rhesus macaques of different geographic origin is not currently known, and there is only limited information on Mamu-A allele sharing.…”
Section: Potential Admixture Of Chinese-and Indian-origin Rhesus Macasupporting
confidence: 87%
“…Of these 41 sequences, 8 had been previously reported in rhesus macaques of Indian origin with at least partial cDNA sequences already available in GenBank. In addition, six were identical to alleles recently reported in Chinese rhesus macaques (Otting et al 2007). The remaining 27 cDNAs described in this study have not been reported previously.…”
Section: Summary Of Mhc Class I Cdnas Identifiedsupporting
confidence: 77%
See 1 more Smart Citation
“…But the critical reagents for vaccine research, such as MHC class I tetramers, are currently only designed on the immunogenetic background of Indian rhesus macaques, while the two geographic macaque populations share few common MHC class I alleles (2,10,(17)(18)(19). This study was intended to set up a procedure for constructing new tetramers on the immunogenetic background of Chinese macaques.…”
Section: Discussionmentioning
confidence: 99%
“…Before entering the study, all animals were confirmed to be negative for simian immunodeficiency virus (SIV), simian T-cell lymphotropic virus, and simian retrovirus type D. The MHC class I alleles were determined for all animals. RNA isolation, reverse transcription-PCR (RT-PCR), and cloning and sequencing of macaque class I A and B alleles were described elsewhere (26,27). Unreported alleles, of which at least three full-length clones were present, were submitted to the EMBL-EBI database and also to the nonhuman primate MHC section of the Immuno Polymorphism Database (for official designations, see reference 28).…”
Section: Methodsmentioning
confidence: 99%